2007
DOI: 10.1177/104063870701900116
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pathogens in Ovine and Caprine Abortion Samples from Sardinia, Italy, by PCR

Abstract: Abstract. During 2003During -2005 abortion samples (315 fetuses and 84 placentae) were collected from 107 ovine and caprine farms in northern Sardinia. Tissues from aborted fetuses and placentae were examined by PCR assay to detect DNA from Coxiella burnetii, Chlamydophila abortus, Salmonella enterica Serovar abortusovis, Toxoplasma gondii, and Neospora caninum. The DNA from at least 1 of these 5 infectious agents was amplified in 41% of ovine fetuses, while only 17% of the caprine fetuses yielded a positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
65
1
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 16 publications
11
65
1
14
Order By: Relevance
“…The presence of T. gondii DNA in the placenta, heart and brain of the fetus of a sheep that was positive in the serology confirmed the vertical transmission of the parasite in naturally infected sheep in Brazil. The following data, related to spontaneous abortions caused by T. gondii, are recorded in the literature: 10.6% in Germany (Steuber et al 1995); 11.1% and 18.1% in Italy (Masala et al 2003(Masala et al , 2007; 14.3% in Brazil (Moraes et al 2011);16.9% and23.2% in Spain (Hurtado et al 2001, Pereira-Bueno et al 2004) and 17.5% in the USA (Dubey & Kirkbride 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of T. gondii DNA in the placenta, heart and brain of the fetus of a sheep that was positive in the serology confirmed the vertical transmission of the parasite in naturally infected sheep in Brazil. The following data, related to spontaneous abortions caused by T. gondii, are recorded in the literature: 10.6% in Germany (Steuber et al 1995); 11.1% and 18.1% in Italy (Masala et al 2003(Masala et al , 2007; 14.3% in Brazil (Moraes et al 2011);16.9% and23.2% in Spain (Hurtado et al 2001, Pereira-Bueno et al 2004) and 17.5% in the USA (Dubey & Kirkbride 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, Pereira & Bueno (2004) also demonstrated the presence of Toxoplasma gondii DNA in aborted fetuses from naturally infected sheep. Masala et al (2007) detected T. gondii DNA in the tissues of aborted fetuses in Italy. In Brazil, Moraes et al (2011) found T. gondii in aborted and stillborn sheep fetuses in nested PCR, thereby demonstrating the significance of this disease in sheep reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, congenital neosporosis was described in a goat kid with difficulty rising, ataxia, opistothotonos and non-suppurative encephalitis (Corbellini et al 2001). In Italy, N. caninum was found by PCR in 2 of 23 (8.7%) aborted foetuses (Masala et al 2007). Furthermore, one goat foetus aborted.…”
mentioning
confidence: 99%
“…On the other hand, fetal loss may have non-infectious etiology as well, to mention only mechanical injuries, vitamin and mineral deficiencies and poisonings (Smith and Sherman 2009). As an infectious etiological agent can be identified in a small proportion of cases of fetal loss (Chanton-Greutmann et al 2002, Masala et al 2007, it is suggested that non-infectious causes predominate in etiology of the condition in goats (Waldeland and Løken 1991). An analysis carried out by Engeland et al (1998) indicated inferior natural lighting in the stables, pre-heated drinking water and a building design with a combined feeding and milking platform involving large and crowded pens to be risk factors for non-infectious fetal loss.…”
Section: Introductionmentioning
confidence: 99%